The Extraordinary Solution for Indonesia Economic Crisis: Shariah Capital Market - Widia Astuty (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The historical development of the Islamic finance industry which includes banking, insurance and capital markets is fundamentally a very long historical process. The Islamic Shariah principles applied in the banking industry and Cairo is a country founded the first Islamic bank around 1971 under the name "Nasser Social Bank" operations based on a revenue sharing system (without usury). Islamic principles in muamalah that must be considered by the perpetrators of Islamic investment (related parties) are: l.Do not look for profit in things forbidden, both in terms of substance and how to get it, and do not use it for things that are forbidden. 2. No oppressing and oppressed 3.Justice distribution of prosperity. 3. Transactions carried out on the basis of the same pleasure. No element of riba, may sir and gharar (vagueness). No doubt, to see the development of the Islamic capital market industry is still new. The effect of conventional economic outlook is still strongly felt.Keywords: Economic; Shariah; Indonesia; Capital Market